Legal protection of foreign investor ownership from political risks in the Kurdistan Region (Analysis Study) - Mukhles Salim Murad (Zanco Journal of Humanity Sciences)
The motive that makes most of the developing countries seek foreign investment is that they lack of self-sufficiency of development; that's why most developing countries like Kurdistan Region seek attracting and increasing foreign investment on their land in order to support economic development.